RASIONALISME VS EMPERISME DALAM PERSPEKTIF EPISTEMOLOGI MODERN - Tiara Trirahmayati; Amril Mansur (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This article discusses the debate between rationalism and empiricism from the perspective of modern epistemology, aiming to uncover how both approaches have contributed to the development of science and technology. Rationalism asserts that knowledge is acquired through reason and logic, independent of sensory experience, as advocated by philosophers such as René Descartes and Gottfried Wilhelm Leibniz. In contrast, empiricism emphasizes that knowledge arises from sensory experience, as articulated by John Locke, George Berkeley, and David Hume. Although these views are often considered opposing, Immanuel Kant attempted to bridge the gap by proposing that knowledge is the result of the interaction between reason and experience. In the context of modern science, both rationalism and empiricism are no longer viewed as separate poles but rather as complementary, especially in fields such as artificial intelligence and neurobiology. This article demonstrates that the synthesis of rationalism and empiricism provides a more holistic understanding of human knowledge, which is highly relevant to the advancement of science and technology in the modern era. This research employs a descriptive-analytical qualitative approach, examining literature related to rationalism, empiricism, and modern epistemology to analyze their contributions to the formation of knowledge